Strategi Komunikasi Baznas Kabupaten Batu Bara dalam Program Pinjaman Modal Kelompok Tani di Desa Sumber Tani Kecamatan Datuk Tanah Datar - Karib, Abdur Rauf; Samosir, Hasrat Efendi; Ritonga, Elfi Yanti (Lembaga Yasin AlSys, 2023)
The general objective of this research was to seek and discover the communication strategy of BAZNAS for Batu Bara Regency in carrying out agricultural productive loan programs. The specific objective of this study was to see how the efforts or efforts were made by BAZNAS of Batu Bara Regency in introducing a productive agricultural loan program to farmer groups in Sumber Tani Village, Datuk Tanah Datar District; obstacles that occur in the implementation of the program; and the benefits felt by the community while participating in the agricultural productive loan program from BAZNAS. This study uses a qualitative approach with the aim of obtaining an in-depth description of the data. The research results obtained showed that in the process of implementing the agricultural productive loan program: (1) The planning that was built by BAZNAS of Batu Bara Regency to run the program used a personal approach to someone who was considered to have influence in farmer groups. In addition, BAZNAS also conducts socialization activities which are carried out simultaneously with the distribution of zakat from the farmers' harvest to farmer groups. (2) The obstacles experienced by BAZNAS of Batu Bara Regency in implementing the program are seen from two perspectives. First, the process of providing assistance and returning assistance to BAZNAS has never experienced any problems. Second, in the program introduction process, farmers still have doubts about participating in making loans. (3) The benefit felt by the community from the implementation of the program is that farmers have institutions that can provide interest-free loans so that farmers' crops can be sold to any party.